Stress Management Training Towards Stress Level Reduction in Families of Schizophrenia Patients - Noviana Ayu Ardika; Aisyiyah Mutia Dawis (Universitas Malahayati Lampung, 2026)
ABSTRACT Introduction: Families are individuals who are close to the patient and are considered to have the greatest influence on the patient's life at home. One of the causes of stress in families is caring for patients with schizophrenia at home. During care, families who lack information on how to cope with stress are at greater risk of experiencing burden during care. One of the causes of stress is the length of care for the patient and the patient's behavior due to relapse. Stress management is one way to reduce stress in families at home. Objective: This community service activity is to increase family knowledge in coping with stress in caring for people with schizophrenia at home. Method: The service was carried out through an initial survey, pre-test, interactive lecture, demonstration of deep breathing techniques and five-finger hypnosis, discussion and question and answer, and post-test. Samples were obtained from families with schizophrenia patients at home, with as many as 25 people in the Joyontakan Village area. Results: There was a decrease in stress levels in families with schizophrenia patients at home. The number of respondents with moderate and severe stress decreased from 18 (72%) to 6 (24%), while respondents with normal and mild stress levels increased from 7 (28%) to 19 (76%). Conclusion: Deep breathing and five-finger hypnosis training have been shown to reduce stress levels in families with schizophrenia patients at home. Keywords: Stress Management, Stress Levels, Families Of Schizophrenia Patients.